Imitative Decision Making Information Arrangement Technologies - Rutkauskas, Aleksandras Vytautas; Rutkauskas, Vytautas (Ekonomika, 1999)
The article deals with computerised imitative technologies for generation and arrangement of information to be used in decision making. From one side supposition about point estimated possibilities isn’t adequate to reality. From another side, in the case of opposite supposition some computational problems ought to arise. It is shown in the paper, how to use imitative technologies for solving such problems.